Rola narodów w religijnej formacji Izraela u proroków pisarzy - Homerski, Józef (The Biblical Annals, 2017)
The author deals with the problem of the role played by foreign nations in the religious life of Israel as the people of Yahwe . He examines the prophetic oracles of the Old Testament where the foreign nations were mentioned in a general way i. e. without their names (about 530 vs.). His conclusions are as follows: The idea that the alien nations were a tool of punishment i the hand of God appeared earlier in the prophetic writings than the idea that the alien nations were an object of Yahwe’s salvific care. Punishments and calamities sent by heaven upon sinful nations were a warning or a kind of instruction for Israel that Yahwe was the upright judge of all mankind. The nations, since they witnessed the special care of Yahwe toward the chosen People, exercised a greater or a lesser impact on the implementation of the convenant of Israel. This happened in two ways: negatively (bringing about in Israel feelings of horror, shame or fear of God) and positively (awaking an awarness of the duty to give a good example and to witness for God). In the later prophetic writings the idea emerged that the alien nations were to be gained for Yahwe, but this was more a passive than an active attitude. The prophetic utterences about the nations not mentioned by name were moral and religious admonitions and were not concerned with political affaires. Those admonitions, down the centuries, became more and more eschatological and at the time, they tended to stress the importance of cult.